Affection, Identities and Corporealities - Rebeca Beatriz Cena (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
Love, affectivity, collective identities and affection of the bodies make up inquiry objects from which the production and reproduction of sensibilities are problematized in certain contexts. From the point of view of Social Sciences interested in the study of bodies and emotions, the different ways in which the bodies are affected leads to an elucidation of their reproduction at social level. In other words, problematizing how subjects behave, interact among each other and shape as a consequence of and in certain social contexts.